Occlusal caries prevention in high and low risk schoolchildren. A clinical trial - da Silva Tagliaferro, Elaine Pereira [UNESP]; Pardi, Vanessa; Bovi Ambrosano, Glaucia Maria; Meneghim, Marcelo de Castro; Correa da Silva, Silvio Rocha [UNESP]; Pereira, Antonio Carlos (Mosher & Linder, Inc, 2011)
Purpose: To evaluate the caries-preventive effect of a resin-modified glass-ionomer cement used as occlusal sealant (Vitremer) compared with fluoride varnish (Duraphat) application on occlusal surfaces of permanent first molars (OSPFM) in 6-8 year-old schoolchildren (n=268) at high (HR) and low (LR) caries risk. Methods: The children were followed-up for 24 months after being systematically allocated into six groups as follows: Control Groups HRC and LRC: children receiving oral health education (OHE) every 3 months; Groups HRV and LRV: children receiving OHE plus varnish application biannually; and Groups HRS and LRS: children receiving OHE plus a single sealant application. The baseline and follow-up examinations were performed by the same calibrated dentist under natural light, using CPI probes and mirrors, after toothbrushing and air-drying. The DMFS was used to record dental caries, in addition to the detection of initial lesions (IL). Data analysis was performed with two primary outcome measures: DMF and DMF+IL on the OSPFM. Results: After 24 months, only the HRS group showed statistically lower DMF and DMF+IL increments on OSPFM compared with IIRC group. HRV group did not differ from HRC and HRS groups. For LR groups, no statistical difference (P> 0.05) was observed among the treatments. (Am J Dent 2011;24:109-114).